Universal adaptive control of satellite formation flying - Pongvthithum R. (2014)
In this paper, a new universal adaptive control scheme for satellite formation flying is developed. The underlying idea of our design is to combine the domination design and the monotone adaptive gain. This scheme is guaranteed to have the properties of position tracking and full adaptivity against all parameters. Simulation studies are given which establish that implementation of this scheme would not require unachievable actuator signals. © 2005 Taylor & Francis Ltd.